2018
DOI: 10.1177/0706743718792195
|View full text |Cite
|
Sign up to set email alerts
|

Treatment History of Youth At-Risk for Serious Mental Illness

Abstract: We found that treatment history for participants in the PROCAN study differed among the at-risk groups. Future initiatives focused on determining the effects of treatment history on SMI are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Similar to our previous publication, 3 there were differences between the at-risk clinical stage groups, and by having 2 years of follow-up assessments, we observed that these same treatment patterns persisted over time. The stage 1a and 1b participants reported the highest proportions of medication use, whereas stage 0 participants, although much lower, still reported medication use across the follow-up timepoints.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our previous publication, 3 there were differences between the at-risk clinical stage groups, and by having 2 years of follow-up assessments, we observed that these same treatment patterns persisted over time. The stage 1a and 1b participants reported the highest proportions of medication use, whereas stage 0 participants, although much lower, still reported medication use across the follow-up timepoints.…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported the lifetime history of and current medication treatment for individuals in various stages of risk for an SMI in the Canadian Psychiatric Risk and Outcome Study (PROCAN). 3 We found that not only did treatment history vary by at-risk groups, but that many young people with no formal diagnoses were taking medications, and that some of those young individuals had been taking medications for at least several years. 3 Our aim for this report was to determine whether the same medication treatment patterns persisted through 2 years of the PROCAN follow-up.…”
Section: Introductionmentioning
confidence: 73%
“…Possible treatment effects were not accounted for in the present analyses. Approximately one‐third of individuals in the Stage 1a (32.7%) and 1b (34.3%) groups had been prescribed with either antidepressants or stimulants . About a half of the 1b (49.1%) and a quarter of 1a participants (26.9%) received psychosocial therapy (for a detailed report see tables 2 and 3 in Farris et al .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Housing and employment status, level of education, and socioeconomic status have all been associated with increased risk of mental health disorders. [10][11][12][13][14] Increasing evidence suggests that when mental health problems are not effectively treated within the context of a person's needs, they can impair self-care and adherence to medical and mental health treatments, and improperly treated mental health problems are associated with increased morbidity and mortality, increased health care costs, and decreased productivity. [15][16][17][18][19] As Patel and colleagues note, the rationale for coordinated health services for people with mental illness includes improving access to mental health care, providing patient-centred care, avoiding fragmentation of health services, reducing stigma, optimizing both mental and physical health outcomes, and strengthening the overall health system.…”
Section: Points De Repère Du Rédacteurmentioning
confidence: 99%